HYGIENIC ASSESSMENT OF THE NUTRITIONAL STATUS OF POSTTERM CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this study, the nutritional characteristics and physical development indicators of 50 post-term infants were examined. According to the research results, 32% of the children were fed with artificial nutrition, while 34% had a mixed feeding pattern. Among them, 42.0% were breastfed up to one year of age, and 58.0% continued breastfeeding up to two years. Regarding the number of daily meals, 58.0% of the children ate 1–4 times per day. Additionally, 58.0% of the children received supplementary feeding up to 6 months of age. In terms of food consumption levels, 48.0% of the children consumed bread, cereals, porridge, and grain-based foods in excess of the recommended amount, while 36.0% consumed foods containing salt and sugar above the normal limit. The findings of the study revealed that most post-term infants had disrupted eating patterns. This condition may contribute to delayed physical development and an increased incidence of various diseases among these children.